Perancangan Sistem Pengenalan Wajah Dengan Metode CNN Pada Sistem Keamanan Door Lock Pintu Kamar Hotel - Anwariyah, Komariyuli; Hariani, Yuni Sulpia; Budiman; MZ, Dedy Sofian (LPPM Universitas Negeri Semarang, 2024)
Room door lock security can be managed using conventional techniques or automated systems. Currently, most hotels in Indonesia, particularly in the Lombok area, utilize card keys for room access. This method is effective and convenient, as guests do not need to carry physical keys. However, there are instances when guests forget to take their card when leaving the room, which complicates re-entering their accommodations. One potential solution is to implement the Convolutional Neural Network (CNN) method for recognition. The CNN process involves four key stages: area detection, feature extraction, matching, and recognition. Tests conducted on this system indicate that the CNN method can accurately recognize provided input images. Out of 10 images tested, 90% were recognized successfully. The results suggest that the CNN method is a promising option for enhancing room lock security